A low-leakage plastic liner all-carbon fiber wrapped gas cylinder and preparation method thereof

By adding reinforced polymer and winding carbon fiber layer to the plastic inner liner, the problems of hydrogen leakage and low-temperature brittleness of the fourth-generation plastic inner liner full fiber winding cylinder under high pressure are solved, achieving higher sealing and service life.

CN119391177BActive Publication Date: 2025-04-08SHENYANG OUSHIDUN NEW MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510006677.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The existing fourth-generation plastic inner liner full fiber wrapping gas cylinder is prone to cause hydrogen leakage under high pressure, and its brittleness increases under low temperature conditions, resulting in reduced sealing and shortened service life.

Method used

Reinforced polymers are prepared by polymerizing acrylic and/or acrylic derivatives with crosslinking agents, and added to the plastic inner liner to improve sealing and low-temperature impact resistance, while wrapping the carbon fiber layer on the outside to enhance the overall performance of the cylinder.

Benefits of technology

It significantly reduces the leakage of hydrogen, improves the low-temperature impact resistance and sealing of the cylinder, thereby extending the service life and safety of the cylinder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses a low-leakage plastic liner full carbon fiber wrapped gas cylinder and its preparation method, which belongs to the technical field of hydrogen storage gas cylinder preparation. The gas cylinder comprises: a plastic liner: by weight, the plastic liner comprises 80-100 parts of PA6, 8-15 parts of EVOH, 10-20 parts of epoxy resin, 15-20 parts of reinforcing polymer, 2-3 parts of curing agent and 2-5 parts of plasticizer; a fiber winding layer: the fiber winding layer is arranged on the outside of the plastic liner; the reinforcing polymer is obtained by polymerization of acrylic acid and / or acrylic acid derivatives, a cross-linking agent under an initiator and a catalyst. The improvement of the plastic liner in the gas cylinder can improve the sealing and low-temperature impact resistance of the gas cylinder, and extend the service life and safety of the plastic liner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a low-leakage plastic liner all-carbon fiber wrapped gas cylinder and a preparation method thereof, belonging to the technical field of hydrogen storage gas cylinder preparation. Background Art

[0002] High-pressure hydrogen storage technology refers to the technology of compressing hydrogen under high pressure and storing it in a high-density gaseous form in a hydrogen storage cylinder. Generally, the pressure of a hydrogen storage cylinder is 35~70MPa. At present, the fourth-generation plastic liner full-fiber wrapped cylinder has become an urgent need for the large-scale promotion and use of hydrogen fuel cell electric vehicles due to its advantages such as light weight, large capacity and corrosion resistance.

[0003] Currently, the fourth generation of plastic liners is made of polyethylene and / or polyamide materials. However, such materials will cause the gas to diffuse out of the plastic liner due to Brownian motion under high pressure, resulting in hydrogen leakage, and will cause cracks or bulges in the plastic liner during the inflation or deflation process. All of the above will reduce the sealing of the hydrogen storage cylinder and reduce the service life of the cylinder. In addition, the temperature of the hydrogen storage cylinder varies in the range of -40~85℃ during inflation and deflation. If the low-temperature impact resistance of the plastic liner is not enough, the brittleness of the plastic liner will increase at low temperatures, which will also reduce the service life of the hydrogen storage cylinder. Summary of the invention

[0004] In order to solve the above problems, a low-leakage plastic liner full carbon fiber wrapped gas cylinder and a preparation method thereof are provided. The gas cylinder consists of a plastic liner and a fiber winding layer. The improvement of the plastic liner can improve the sealing of the gas cylinder, reduce the leakage of hydrogen, and improve the low-temperature impact resistance of the plastic liner, thereby extending the service life and safety of the plastic liner.

[0005] According to one aspect of the present application, a low-leakage plastic liner all-carbon fiber wrapped gas cylinder is provided, comprising:

[0006] Plastic liner: by weight, the plastic liner comprises 80-100 parts of PA6, 8-15 parts of EVOH, 10-20 parts of epoxy resin, 15-20 parts of reinforcing polymer, 2-3 parts of curing agent and 2-5 parts of plasticizer;

[0007] Fiber winding layer: the fiber winding layer is arranged on the outer side of the plastic liner;

[0008] The reinforcing polymer is obtained by polymerizing acrylic acid and / or acrylic acid derivatives and a crosslinking agent in the presence of an initiator and a catalyst.

[0009] The reinforced polymer prepared by polymerization of acrylic acid and / or acrylic acid derivatives and a crosslinking agent can toughen the PA6 matrix under the above ratio, absorb impact energy when the gas cylinder is impacted during the filling and deflation process, and evenly disperse the absorbed energy along the polymer network, thereby improving the low-temperature impact resistance and deformation resistance of the plastic liner. In addition, the above-mentioned reinforced polymer can cooperate with the substrate to jointly improve the sealing of the gas cylinder. If the amount of the reinforced polymer added is too much, the strength of the plastic liner will be reduced. If the amount of the reinforced polymer added is too little, the low-temperature impact resistance and sealing of the gas cylinder cannot be effectively improved.

[0010] Optionally, the reinforcing polymer is obtained by polymerizing acrylic acid, acrylic acid derivatives and a crosslinking agent in a molar ratio of (1.5-3):1:0.01 in the presence of an initiator and a catalyst.

[0011] Under the above ratio, the molecular chains of acrylic acid and acrylic acid derivatives have moderate degrees of freedom and can be evenly dispersed in the PA6 matrix, thereby improving the density of the plastic liner and improving the compatibility with the PA6 matrix, thereby enhancing the mechanical strength of the plastic liner.

[0012] Optionally, the acrylic acid derivative is selected from at least one of diethylene glycol diacrylate, triethylene glycol diacrylate and tetraethylene glycol diacrylate.

[0013] Optionally, the acrylic acid derivative is selected from triethylene glycol diacrylate.

[0014] The above-mentioned acrylic acid derivatives all contain ester groups and ether groups, which can increase the compatibility with epoxy resin and reduce the degree of microphase separation with epoxy resin, thereby improving the uniformity of the plastic liner, further toughening the plastic liner, and synergistically improving the sealing of the gas cylinder in combination with epoxy resin.

[0015] Optionally, the crosslinking agent is prepared from monomer A and acryloyl chloride, wherein monomer A contains a compound having at least three -NH2 groups.

[0016] The amide group is generated by the reaction of monomer A and acryloyl chloride. The double bond in acryloyl chloride participates in the cross-linking reaction. The introduction of the amide group can improve the strength of the plastic liner, and some amide groups can also react with epoxy resin, so that the reinforcing polymer and epoxy resin form an interpenetrating cross-linked network structure. Therefore, when the plastic liner is impacted, the interpenetrating cross-linked network conduction can absorb the impact force and disperse the impact force, thereby improving the low-temperature impact resistance of the plastic liner. In addition, since the reinforcing polymer contains amide groups, the amide groups will also react with epoxy resin during the injection molding preparation of the plastic liner, so the strength of the plastic liner can also be enhanced.

[0017] Optionally, the monomer A is selected from one of tris(amino-PEG3-amide)-amine (CAS: CAS: 2523025-40-1), tris(amino-PEG4-amide)-amine (CAS: 2523025-41-2), and tris(amino-PEG5-amide)-amine (CAS: 2055013-52-8).

[0018] The structure of the above-mentioned monomer A contains carbonyl and ether groups, which can also improve the compatibility with epoxy resin, thereby improving the toughening effect. In addition, the structure is similar to the combination with acrylic acid derivatives, which can increase the affinity with acrylic acid derivatives, thereby improving the reaction activity of the reinforced polymer and improving the yield.

[0019] Optionally, the preparation method of the cross-linking agent is:

[0020] The monomer A is added to the solvent, and then a neutralizing agent is added and stirred evenly, and finally acryloyl chloride is added, and the mixture is reacted at 20-30° C. for 5-7 hours to obtain the crosslinking agent.

[0021] Preferably, the molar ratio of monomer A to acryloyl chloride is 1:(3.5-4.5).

[0022] Optionally, the neutralizing agent is selected from at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate.

[0023] According to another aspect of the present application, a method for preparing a low-leakage plastic liner all-carbon fiber wrapped gas cylinder as described in any of the above items is provided, comprising the following steps:

[0024] (1) weighing the raw materials of the plastic liner according to the ratio and mixing them evenly, and forming the plastic liner by injection molding;

[0025] (2) The carbon fiber is impregnated in an impregnation slurry to obtain an impregnated fiber, the impregnated fiber is wound around the outside of the plastic liner, heated and cured to form a fiber winding layer, and a bottle mouth joint is installed at the bottle mouth.

[0026] Optionally, the impregnation slurry includes 50-60 parts of waterborne epoxy resin and 2-5 parts of curing agent.

[0027] Preferably, the impregnation slurry further comprises 5 parts of a flame retardant additive and 5 parts of ethanol, and the preparation method of the flame retardant additive is:

[0028] 1) Add p-nitrobenzoic acid and thionyl chloride in a molar ratio of 1:(2.5-3) to a solvent, react at 60-70°C for 10-12 hours, remove excess thionyl chloride under reduced pressure to obtain p-nitrobenzoyl chloride;

[0029] 2) dissolving p-nitrobenzoyl chloride in a solvent to obtain solution A, dissolving dihydroxy monomer and triethylamine in a solvent to obtain solution B, wherein the molar ratio of p-nitrobenzoyl chloride, dihydroxy monomer and triethylamine is 1:(2-3):(2-3), adding solution B dropwise to solution A at room temperature, reacting at 20-30° C. for 8-10 hours, filtering, washing and drying to obtain intermediate A;

[0030] 3) Add intermediate A and stannous chloride dihydrate in a molar ratio of 1:(1.5-3) to a solvent, react at 50-70°C for 15-20h, then add 5% sodium bicarbonate solution to adjust the solution to alkalinity, filter, separate, distill under reduced pressure, and dry to obtain intermediate B;

[0031] 4) The intermediate B and tris(2,3-dichloropropyl) phosphate in a molar ratio of (3-4):1 are placed in a solvent, heated under reflux for 20-24 hours to obtain the obtained product, and then distilled under reduced pressure, extracted, and dried to obtain the obtained product.

[0032] The dihydroxy monomer is selected from at least one of 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol and 1,6-hexanediol.

[0033] By introducing a flame retardant additive into the impregnation slurry, the flame retardant additive contains phosphate groups and chlorine atoms, which can improve the flame retardancy of the gas cylinder. The flame retardant additive contains excess amino groups. Compared with other flame retardant additives, it can react with epoxy resin and act as a cross-linking agent for epoxy resin to form a dense and uniform fiber winding layer, thereby improving the flame retardancy and flame retardancy uniformity of the gas cylinder. In addition, the benzene ring structure contained in the flame retardant additive can improve the durability of the fiber winding layer, and the ester structure improves the toughness with the epoxy resin. The above effects synergistically increase the service life of the gas cylinder.

[0034] Optionally, the thickness of the plastic liner is 5-6 mm, the thickness of the fiber winding layer is 25-30 mm, and the amount of the glue impregnation is 20wt%-30wt%.

[0035] Optionally, the injection temperature of the plastic liner is above the melting point, preferably 15-20° C. above the melting point, the curing temperature for forming the fiber winding layer is 120° C., and the curing time is 6 hours.

[0036] The beneficial effects of this application include but are not limited to:

[0037] 1. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder of the present application can improve the compatibility of various raw materials of the plastic liner and the peel strength of the gas cylinder by introducing reinforcing polymers into the plastic liner, thereby extending the service life of the gas cylinder.

[0038] 2. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder of the present application uses a reinforced polymer of acrylic acid and / or acrylic acid derivatives to reinforce the plastic liner, which can improve the low-temperature impact resistance of the gas cylinder while improving its sealing performance, thereby improving the safety of the gas cylinder during the filling and deflation process.

[0039] 3. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder of the present application, the reinforcing polymer is obtained by polymerization of acrylic acid, acrylic acid derivatives and cross-linking agents in a suitable molar ratio, which can toughen the plastic liner and form an interpenetrating cross-linking network with epoxy resin to improve the toughness of the plastic liner. DETAILED DESCRIPTION

[0040] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0041] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.

[0042] The curing agent in the present application can be any one or more of an alkaline curing agent and an acidic curing agent, and the plasticizer, initiator and catalyst can also be selected from existing plasticizers, initiators and catalysts in the prior art. The specific types of the above curing agent, plasticizer, initiator and catalyst do not constitute a limitation to the present application. In the following embodiments, diethylenetriamine is used as a curing agent, dibutyl phthalate is used as a plasticizer, ammonium persulfate is used as an initiator, and N,N,N',N'-tetramethyl-ethylenediamine is used as a catalyst.

[0043] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art. The solvents used may be methanol, ethanol, DMF, DMSO, ethyl acetate, chloroform, dichloromethane, acetone, etc. The type of solvent used does not limit the reaction process, so in the following examples, a suitable solvent can be selected according to the properties of the raw materials and actual needs.

[0044] Example 1

[0045] This embodiment relates to the preparation of a reinforced polymer, which specifically includes the following steps:

[0046] Acrylic acid, acrylic acid derivatives and cross-linking agents in a molar ratio of (1.5-3): 1:0.01 are mixed in a solvent at room temperature, and an initiator accounting for 1.0 wt% of acrylic acid and a catalyst accounting for 1.0 wt% of acrylic acid are added. After stirring evenly, the temperature is raised to 35°C for reaction for 10 minutes, and then poured into a mold and vacuum cured at 80°C for 12 hours to obtain the product.

[0047] Preferably, the acrylic acid derivative is selected from at least one of diethylene glycol diacrylate, triethylene glycol diacrylate and tetraethylene glycol diacrylate.

[0048] Preferably, the crosslinking agent is prepared from monomer A and acryloyl chloride. The preparation method of the crosslinking agent is: adding monomer A to a solvent, then adding a neutralizing agent and stirring evenly, and finally adding acryloyl chloride, and reacting at 20-30° C. for 5-7 hours to obtain a compound in which monomer A contains at least three -NH2 groups.

[0049] More preferably, monomer A is selected from one of tris(amino-PEG3-amide)-amine, tris(amino-PEG4-amide)-amine, and tris(amino-PEG5-amide)-amine.

[0050] The following enhanced polymer was prepared according to the above preparation method, as follows:

[0051] Reinforced polymer 1#:

[0052] S1: Tris(amino-PEG3-amide)-amine was added to the solvent, followed by adding sodium hydroxide and stirring, and finally adding acryloyl chloride, and reacting at 30°C for 5 hours to obtain crosslinker 1#, wherein the molar ratio of tris(amino-PEG3-amide)-amine to acryloyl chloride was 1:3.5, and the molar ratio of sodium hydroxide to acryloyl chloride was 1.5:1;

[0053] S2: Acrylic acid, diethylene glycol diacrylate and crosslinking agent 1# are mixed in a solvent at a molar ratio of 1.5:1:0.01 at room temperature, and an initiator accounting for 1.0wt% of acrylic acid and a catalyst accounting for 1.0wt% of acrylic acid are added. After stirring evenly, the temperature is raised to 35°C for reaction for 10 minutes, and then poured into a mold, and vacuum cured at 80°C for 12 hours to obtain reinforced polymer 1#.

[0054] Reinforced polymer 2#:

[0055] S1: Tris(amino-PEG5-amide)-amine was added to the solvent, followed by sodium carbonate and stirring, and finally acryloyl chloride was added and reacted at 20°C for 7 hours to obtain crosslinker 2#, wherein the molar ratio of tris(amino-PEG5-amide)-amine to acryloyl chloride was 1:4.5, and the molar ratio of sodium carbonate to acryloyl chloride was 1.5:1;

[0056] S2: Acrylic acid, tetraethylene glycol diacrylate and crosslinking agent 2# are mixed in a solvent at a molar ratio of 3:1:0.01 at room temperature, and an initiator accounting for 1.0wt% of acrylic acid and a catalyst accounting for 1.0wt% of acrylic acid are added. After stirring evenly, the temperature is raised to 35°C for reaction for 10 minutes, and then poured into a mold, and vacuum cured at 80°C for 12 hours to obtain reinforced polymer 2#.

[0057] Reinforced polymer 3#:

[0058] S1: Tris(amino-PEG4-amide)-amine was added to the solvent, followed by sodium bicarbonate and stirring, and finally acryloyl chloride was added and reacted at 25°C for 6 hours to obtain crosslinker 3#, wherein the molar ratio of tris(amino-PEG4-amide)-amine to acryloyl chloride was 1:4, and the molar ratio of sodium bicarbonate to acryloyl chloride was 1.5:1;

[0059] S2: Acrylic acid, triethylene glycol diacrylate and crosslinking agent 3# are mixed in a solvent at a molar ratio of 2:1:0.01 at room temperature, and an initiator accounting for 1.0wt% of acrylic acid and a catalyst accounting for 1.0wt% of acrylic acid are added. After stirring evenly, the temperature is raised to 35°C for reaction for 10 minutes, and then poured into a mold, and vacuum cured at 80°C for 12 hours to obtain reinforced polymer 3#.

[0060] Reinforced polymer 4#:

[0061] The difference between the present enhanced polymer and enhanced polymer 3# is that triethylene glycol diacrylate is replaced by acrylic acid, that is, only acrylic acid and crosslinking agent 3# react, and the rest is the same as enhanced polymer 3#.

[0062] Reinforced polymer 5#:

[0063] The difference between the present enhanced polymer and enhanced polymer 3# is that acrylic acid is replaced by triethylene glycol diacrylate, that is, only triethylene glycol diacrylate and crosslinking agent 3# react, and the rest is the same as enhanced polymer 3#.

[0064] Reinforced polymer 6#:

[0065] The difference between the present reinforced polymer and reinforced polymer 3# is that triethylene glycol diacrylate is replaced by tetraethylene glycol diacrylate, and the rest is the same as reinforced polymer 3#.

[0066] Reinforced polymer 7#:

[0067] The difference between the present reinforced polymer and reinforced polymer 3# is that the molar ratio of acrylic acid to triethylene glycol diacrylate is 1:2, and the rest is the same as reinforced polymer 3#.

[0068] Reinforced polymer 8#:

[0069] The difference between this enhanced polymer and enhanced polymer 3# is that tri(amino-PEG4-amide)-amine is replaced by 1,3,5-triaminobenzene, and the rest is the same as enhanced polymer 3#.

[0070] Example 2

[0071] This embodiment relates to a method for preparing a low-leakage plastic liner all-carbon fiber wrapped gas cylinder, comprising the following steps:

[0072] (1) Weighing and mixing the raw materials of the plastic liner in a ratio of 80-100 parts of PA6, 10-20 parts of epoxy resin, 10-15 parts of reinforcing polymer, 2-3 parts of curing agent and 2-5 parts of plasticizer, and performing injection molding above the melting point to obtain a plastic liner with a thickness of 5-6 mm;

[0073] (2) 50-60 parts of water-based epoxy resin and 2-5 parts of curing agent are mixed to form an impregnation slurry, carbon fiber is impregnated in the impregnation slurry to obtain impregnated fiber, the impregnated fiber is wound around the outside of the plastic liner, the impregnation amount of the impregnated fiber is 20wt%-30wt%, heated to 120°C and cured for 6 hours to form a fiber winding layer with a thickness of 25-30mm, and a bottle mouth joint is installed at the bottle mouth.

[0074] The following gas cylinders were prepared according to the above preparation method, with the following specific differences:

[0075] Gas cylinder 1#:

[0076] (1) Weigh the raw materials of the plastic liner according to the ratio of 80 parts of PA6, 10 parts of epoxy resin, 10 parts of reinforced polymer 1#, 2 parts of curing agent and 2 parts of plasticizer, mix them evenly, and injection mold them above the melting point to obtain a plastic liner with a thickness of 5 mm;

[0077] (2) 50 parts of water-based epoxy resin and 2 parts of curing agent are mixed to form an impregnation slurry, carbon fiber is impregnated in the impregnation slurry to obtain impregnated fiber, the impregnated fiber is wound around the outside of the plastic liner, the impregnation amount of the impregnated fiber is 20wt%, heated to 120°C and cured for 6 hours to form a fiber winding layer with a thickness of 25mm, and a bottle mouth joint is installed at the bottle mouth.

[0078] Gas cylinder 2#:

[0079] (1) The raw materials of the plastic liner are weighed and mixed evenly according to the ratio of 100 parts of PA6, 20 parts of epoxy resin, 15 parts of reinforced polymer 2#, 3 parts of curing agent and 5 parts of plasticizer, and injection molding is performed above the melting point to obtain a plastic liner with a thickness of 6 mm;

[0080] (2) 60 parts of water-based epoxy resin and 5 parts of curing agent are mixed to form an impregnation slurry, carbon fiber is impregnated in the impregnation slurry to obtain impregnated fiber, the impregnated fiber is wound around the outside of the plastic liner, the impregnation amount of the impregnated fiber is 30wt%, heated to 120°C and cured for 6 hours to form a fiber winding layer with a thickness of 30mm, and a bottle mouth joint is installed at the bottle mouth.

[0081] Gas cylinder 3#:

[0082] The difference between this gas cylinder and gas cylinder 2# is that reinforced polymer 3# is used to replace reinforced polymer 2#, and the rest is the same as gas cylinder 2#.

[0083] Gas cylinder 4#:

[0084] The difference between this gas cylinder and gas cylinder 2# is that reinforced polymer 4# is used to replace reinforced polymer 2#, and the rest is the same as gas cylinder 2#.

[0085] Gas cylinder 5#:

[0086] The difference between this gas cylinder and gas cylinder 2# is that reinforced polymer 5# is used to replace reinforced polymer 2#, and the rest is the same as gas cylinder 2#.

[0087] Gas cylinder 6#:

[0088] The difference between this gas cylinder and gas cylinder 2# is that reinforced polymer 6# is used to replace reinforced polymer 2#, and the rest is the same as gas cylinder 2#.

[0089] Gas cylinder 7#:

[0090] The difference between this gas cylinder and gas cylinder 2# is that reinforced polymer 7# is used to replace reinforced polymer 2#, and the rest is the same as gas cylinder 2#.

[0091] Gas cylinder 8#:

[0092] The difference between this gas cylinder and gas cylinder 2# is that reinforced polymer 8# is used to replace reinforced polymer 2#, and the rest is the same as gas cylinder 2#.

[0093] Compare gas cylinder D1#:

[0094] The difference between this comparison gas cylinder and gas cylinder 2# is that the reinforced polymer 2# is not added to the plastic liner, and the rest is the same as gas cylinder 2#.

[0095] Test Example 1

[0096] Impact tests were performed on the plastic liners prepared in Example 2 to obtain the room temperature notched impact strength and the -40°C notched impact strength of the plastic liners.

[0097] The gas cylinders prepared in the above Example 2 were then subjected to hydrogen permeability coefficient, fatigue life test and peel strength test, wherein the hydrogen permeability coefficient was carried out in accordance with GB / T42610-2023; the fatigue life test was carried out in accordance with GB / T42612-2023. In the peel strength test, the gas cylinder was cut into strips with a width of 150 mm × 200 mm, and the plastic liner and the fiber winding layer were pre-peeled 50 mm along the length direction. The sample was placed in an environment with a temperature of 23±2°C and a relative humidity of 50±5% for 4 days, and the two ends of the peeled part of the sample were clamped on the upper and lower clamps of the tensile testing machine, respectively, so that the peeled part of the sample was in a vertical state and the unpeeled part was in a horizontal state. The testing machine was turned on for peeling, and the test speed was set to 100 mm / min, and its peel strength was calculated.

[0098] The specific test results are shown in Table 1 below:

[0099] Table 1

[0100]

[0101] Example 3

[0102] In this embodiment, 5 parts of flame retardant additive and 5 parts of ethanol are added to the impregnation slurry of gas cylinder 3# to obtain the following gas cylinder:

[0103] Gas cylinder 9#:

[0104] The preparation method of the flame retardant additive added to gas cylinder 9# is as follows:

[0105] 1) p-nitrobenzoic acid and thionyl chloride in a molar ratio of 1:2.5 are added to a solvent, the reaction time is 10 hours at 70°C, and the excess thionyl chloride is removed under reduced pressure to obtain p-nitrobenzoyl chloride;

[0106] 2) dissolving p-nitrobenzoyl chloride in a solvent to obtain solution A, dissolving 1,6-hexanediol and triethylamine in a solvent to obtain solution B, wherein the molar ratio of p-nitrobenzoyl chloride, 1,6-hexanediol and triethylamine is 1:3:2, and adding solution B dropwise to solution A at room temperature, and then reacting at 20°C for 10 hours, filtering, washing and drying to obtain intermediate A;

[0107] 3) Add intermediate A and stannous chloride dihydrate in a molar ratio of 1:1.5 to a solvent, react at 50°C for 20 hours, then add 5% sodium bicarbonate solution to adjust the solution to alkalinity, filter, separate, distill under reduced pressure, and dry to obtain intermediate B;

[0108] 4) The intermediate B and tris(2,3-dichloropropyl) phosphate in a molar ratio of 3:1 are placed in a solvent, heated under reflux for 24 hours to obtain the obtained product, and then distilled under reduced pressure, extracted, and dried to obtain the obtained product.

[0109] The rest of the preparation method of gas cylinder 9# is the same as that of gas cylinder 3#.

[0110] Gas cylinder 10#:

[0111] The preparation method of the flame retardant additive added to gas cylinder 10# is as follows:

[0112] 1) Add p-nitrobenzoic acid and thionyl chloride in a molar ratio of 1:3 to a solvent, react at 60°C for 12 hours, and remove excess thionyl chloride under reduced pressure to obtain p-nitrobenzoyl chloride;

[0113] 2) dissolving p-nitrobenzoyl chloride in a solvent to obtain solution A, dissolving 1,3-propylene glycol and triethylamine in a solvent to obtain solution B, wherein the molar ratio of p-nitrobenzoyl chloride, 1,3-propylene glycol and triethylamine is 1:2:3, and adding solution B dropwise to solution A at room temperature, and then reacting at 30°C for 8 hours, filtering, washing and drying to obtain intermediate A;

[0114] 3) Add intermediate A and stannous chloride dihydrate in a molar ratio of 1:3 to a solvent, react at 70°C for 15 hours, then add 5% sodium bicarbonate solution to adjust the solution to alkalinity, filter, separate, distill under reduced pressure, and dry to obtain intermediate B;

[0115] 4) The intermediate B and tris(2,3-dichloropropyl) phosphate in a molar ratio of 4:1 are placed in a solvent, heated under reflux for 20 hours to obtain the obtained product, and then distilled under reduced pressure, extracted, and dried to obtain the obtained product.

[0116] The rest of the preparation method of gas cylinder 10# is the same as that of gas cylinder 3#.

[0117] Test Example 2

[0118] Flame retardancy test was conducted on gas cylinders 3#, 9# and 10#. The gas cylinders were cut into 10×10cm specimens and fire resistance test was conducted. The specimens were exposed to the flame of the oil pan for 60s to observe whether the specimens burned. If there was a flame in the gas cylinder, the flame extinguishing time was observed after the fire source was removed. The test results are shown in Table 2.

[0119] Table 2

[0120]

[0121] The gas cylinders prepared in the above-mentioned Examples 2 and 3 were subjected to corrosion resistance and aging resistance tests, and the above-mentioned gas cylinders can meet the corrosion resistance and aging resistance requirements of hydrogen cylinders in the industry.

[0122] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A low-leakage plastic liner all-carbon fiber wrapped gas cylinder, characterized in that: include: Plastic liner: by weight, the plastic liner comprises 80-100 parts of PA6, 8-15 parts of EVOH, 10-20 parts of epoxy resin, 15-20 parts of reinforcing polymer, 2-3 parts of curing agent and 2-5 parts of plasticizer; Fiber winding layer: the fiber winding layer is arranged on the outer side of the plastic liner; The reinforced polymer is obtained by polymerizing acrylic acid and / or acrylic acid derivatives and a crosslinking agent in the presence of an initiator and a catalyst, wherein the acrylic acid derivative is selected from at least one of diethylene glycol diacrylate, triethylene glycol diacrylate, and tetraethylene glycol diacrylate, and the crosslinking agent is prepared from a monomer A and acryloyl chloride in a molar ratio of 1: (3.5 4.5), wherein the monomer A contains a compound of at least three -NH2 groups.

2. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to claim 1, characterized in that: The reinforced polymer is obtained by polymerizing acrylic acid, acrylic acid derivatives and a crosslinking agent in a molar ratio of (1.5-3):1:0.01 in the presence of an initiator and a catalyst.

3. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to claim 1, characterized in that: The acrylic acid derivative is selected from triethylene glycol diacrylate.

4. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to claim 1, characterized in that: The monomer A is selected from one of tris(amino-PEG3-amide)-amine, tris(amino-PEG4-amide)-amine, and tris(amino-PEG5-amide)-amine.

5. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to claim 1, characterized in that: The preparation method of the cross-linking agent is: The monomer A is added to the solvent, and then a neutralizing agent is added and stirred evenly, and finally acryloyl chloride is added, and the mixture is reacted at 20-30° C. for 5-7 hours to obtain the crosslinking agent.

6. The low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to claim 5, characterized in that: The neutralizing agent is selected from at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate.

7. A method for preparing a low-leakage plastic liner all-carbon fiber wrapped gas cylinder, applied to the low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to any one of claims 1 to 6, characterized in that: The steps include: (1) weighing the raw materials of the plastic liner according to the ratio and mixing them evenly, and forming the plastic liner by injection molding; (2) The carbon fiber is impregnated in an impregnation slurry to obtain an impregnated fiber, the impregnated fiber is wound around the outside of the plastic liner, heated and cured to form a fiber winding layer, and a bottle mouth joint is installed at the bottle mouth.

8. The method for preparing a low-leakage plastic liner all-carbon fiber wrapped gas cylinder according to claim 7, characterized in that: The impregnation slurry includes 50-60 parts of waterborne epoxy resin and 2-5 parts of curing agent.

Citation Information

Patent Citations

  • High-pressure hydrogen storage bottle with prepreg tape wound around plastic liner and manufacturing method thereof

    CN111102465A

  • Corrosion-resistant and anti-aging gas storage cylinder as well as manufacturing method and application thereof

    CN117739256A